Respuesta :

Step-by-step explanation:

  • 36-5x=5-6(x-4)

36-5x=5-6x+24

-5x+6x=24+5-36

x=29-36

x=-7

Answer:

x = -7

Explanation:

36 − 5x = 5 − 6(x − 4)

[ Simplify both sides of the equation ]

36 − 5x = 5 − 6(x − 4)

36 + −5x = 5 + (−6)(x) + (−6)(−4) [ Distribute ]

36 + −5x = 5 + −6x + 24

−5x + 36 = (−6x) + (5 + 24) [ Combine Like Terms ]

−5x + 36 = −6x + 29

−5x + 36 = −6x + 29

[ Step 2: Add 6x to both sides ]

−5x + 36 + 6x = −6x + 29 + 6x

x + 36 = 29

[ Step 3: Subtract 36 from both sides ]

x + 36 − 36 = 29 − 36

x = −7